Open Inquiry Module on Energy Transformation to Improve Creative Thinking and Collaboration - Putri Dian Lestari; Haeruddin Haeruddin; Nurjannah Nurjannah; Jusman Mansyur; Amiruddin Kade (Jurnal Ilmiah Pendidikan Fisika, 2025)
The current energy transformation module does not support the application of the open inquiry approach, thus inhibiting students' skills. So, this study aims to develop an open inquiry energy transformation practicum module to improve creative thinking and collaboration skills. The development method used is research and development with the ADDIE model. Limited time and resources were considered, so a more in-depth evaluation was conducted in a follow-up study to evaluate the long-term impact of this module. The research was conducted at SMP IT Qurrota A'yun Palu in November 2024. The sample used was 1 class, namely class VIII D, totaling 30 students. The instruments used are tests, observations, and questionnaires. The test is in the form of a description to measure creative thinking skills. The researchers use observations to assess collaboration skills. Questionnaires for peer assessment of collaboration skills. Questionnaires are also for teacher and learner responses. The study found that the module's validation was 82.15%, categorised as valid. Teacher and student responses were 86.36% and 86.08%, respectively, in the very feasible category. Small group trials rated 92.01%, which was also very feasible, with some suggestions. Large group trials showed that the module improved creative thinking skills with an N-gain of 59% in the moderate category. Collaboration skills were assessed with an observer sheet (85.34% in very collaborative) and peer assessment (73.41% in collaborative). In conclusion, the module is valid and feasible for enhancing creative thinking and collaboration skills.